Some Notes on the Translation as an Interpretative Art and Communication as well. Interview with Juraj Vojtek - Juraj Vojtek (Communication Today, 2025)
This interview has been done at the occasion of The Grant Prize delivered by The Lewis Carroll Society of North America to the Slovak edition of Lewis Carroll’s books Alica v krajine zázrakov and Za zrkadlom a s čím sa tam Alica stretla, in English Alice’s Adventures in Wonderland and Through the Looking Glass and What Alice Found There, which were published by Slovart, illustrated by Dušan Kállay, and co-translated by Viera Vojtková a Juraj Vojtek. It presents two main events organised by the Society at the 150th anniversary of publication of the book in England – the introduction of a three volume set (LINDSETH, J. A. (ed.): Alice In a World of Wonderlands. The Translations of Lewis Carroll´s Masterpiece. New Castle, Delaware : Oak Knoll Press and The Lewis Carroll Society of North America, 2015. 2656 p.), and the exhibition of Lewis Carroll’s masterpieces translated into more than 200 languages of the world. It serves to one of the awarded creators of the book, to Full Prof. Juraj Vojtek, as a starting point to give a thought on such questions as what is a translation, what are its limits and what is its place in communication, from the viewpoint of a practical translator.